Students’ Motivation to Complete the Study in the Pandemic Time: Some Reflections for Post Pandemic Era - Leni Fitriani; Dwi Agustina (Universitas Muhammadiyah Semarang, 2022)
Since it was announced by the World Health Organization in March 2020, the Covid-19 pandemic is still happening now. The impacts of the Covid-19 pandemic are also felt greatly in the world of education, especially as the teaching and learning processes at schools and universities are required to be carried out online during the pandemic. This condition affects final semester students who are working on their thesis as the thesis consultation is also done online. In the writers’ department, some students were able to complete the thesis in the pandemic time but some others failed. This made the writers interested to investigate the students’ motivations in completing their study. This article reports the writers’ qualitative study which focused on revealing the students’ motivation in finishing their study. The study was conducted in English Language Education Department at Pekalongan University, Indonesia in the even semester of the academic year 2021/2022.To get the data the writers used structured interviews. The data were then analysed by using content analysis. The findings suggest that students had various types and levels of motivations in completing their study during the pandemic. The writers also believe that it is necessary to reflect on these findings so that both theses writing and supervision in the post pandemic era can be conducted better.